UNDERSTANDING ABOUT LGBT AMONG STUDENT IN A PUBLIC HIGHER LEARNING INSTITUTION - Abdullah, Zakaria; Amat, Salleh (Department of Guidance and Counseling, FIP, Undiksha, 2019)
LGBT culture has permeated into Malaysian society. It permeates society regardless of educational background, religion and even to students and Professionals. The purpose of this study is generally to explore the understanding of LGBT among students in an IPTA. Specifically, to research IPTA students? understanding about LGBT issues and inquire into IPTA students? perception among LGBT groups in Malaysia. The participants included a total of fifteen (15) IPTA students pursuing undergraduate studies were selected using the qualitative methodology was based on a semi-structured interview of LGBT issues. The participants consisting of Malays, Chinese and Indians age range 20 to 23. The study was conducted at an IPTA in Malaysia. The results of this study were analysed using the content analysis method of the respondents' actual sentences. The results of the LGBT understanding study have found themes and codes of understanding of LGBT acronyms, same-sex relationships, bisexual relationships, and gender exchange. Themes and codes relating to perceptions of religion are contrary to human nature, contrary to eastern culture and open-minded. The findings of this study can provide an in-depth understanding of LGBT in public institutions and help stakeholders formulate principles and policies to address LGBT issues.